2023
DOI: 10.3390/agriculture13081622
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches for Forecasting the Best Microbial Strains to Alleviate Drought Impact in Agriculture

Tymoteusz Miller,
Grzegorz Mikiciuk,
Anna Kisiel
et al.

Abstract: Drought conditions pose significant challenges to sustainable agriculture and food security. Identifying microbial strains that can mitigate drought effects is crucial to enhance crop resilience and productivity. This study presents a comprehensive comparison of several machine learning models, including Random Forest, Decision Tree, XGBoost, Support Vector Machine (SVM), and Artificial Neural Network (ANN), to predict optimal microbial strains for this purpose. Models were assessed on multiple metrics, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The negative impact observed in the ANN model underscores the need for careful consideration of storage parameters to mitigate potential risks associated with the proliferation of undesirable microorganisms [57]. The integration of ANN modeling with a focus on the day of storage provides valuable insights into the dynamic nature of microbiological responses in kombucha fresh cheese [58,59]. Figure 13 illustrates the impact of input variables on the relative importance of TP, DPPH, FRAP, and ABTS.…”
Section: The Accuracy Of the Modelmentioning
confidence: 99%
“…The negative impact observed in the ANN model underscores the need for careful consideration of storage parameters to mitigate potential risks associated with the proliferation of undesirable microorganisms [57]. The integration of ANN modeling with a focus on the day of storage provides valuable insights into the dynamic nature of microbiological responses in kombucha fresh cheese [58,59]. Figure 13 illustrates the impact of input variables on the relative importance of TP, DPPH, FRAP, and ABTS.…”
Section: The Accuracy Of the Modelmentioning
confidence: 99%
“…The observed changes in the compositions of microbial genera in response to drought and rehydration likely represented microbial shifts in the whole community [45]. A few studies have also employed machine learning methods for the identification of featured microbial taxa in response to drought [18,46]. The employment of machine learning approaches increased the efficiency in handling high-dimensional microbial data [46].…”
Section: Specific Microbial Taxa In Response To Water Availabilitymentioning
confidence: 99%
“…A few studies have also employed machine learning methods for the identification of featured microbial taxa in response to drought [18,46]. The employment of machine learning approaches increased the efficiency in handling high-dimensional microbial data [46]. However, one drawback of this study was the lack of follow-up studies validating the roles of the identified microbial taxa in response to drought.…”
Section: Specific Microbial Taxa In Response To Water Availabilitymentioning
confidence: 99%
“…Thereby, they aid in the development of more effective soil management strategies, including irrigation practices and the selection of drought-tolerant crops. Marker taxa hold significant potential for application in Synthetic Communities (SynComs), providing an innovative approach for early intervention under challenging environmental conditions, like droughts, to enhance plant resilience and growth [ 10 , 16 ].…”
Section: Introductionmentioning
confidence: 99%